Preparation method of nano metal oxide Ni3V2O8 doped aluminum hydride composite hydrogen supply material

By preparing nanometal oxide Ni3V2O8 doped aluminum hydride composite material, the problems of high hydrogen release temperature and poor kinetic performance of aluminum hydride are solved, and lower hydrogen release temperature and higher hydrogen release volume are achieved. It is suitable for portable fuels Applications in fields such as batteries and drones.

CN119118058AActive Publication Date: 2024-12-13HENAN POLYTECHNIC UNIV +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411247127.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2024-12-13
Estimated Expiration
2044-09-06

AI Technical Summary

Technical Problem

As the hydrogen source of portable fuel cells, aluminum hydride has the problems of high hydrogen release temperature and poor kinetic performance, which limits its practical application in portable fuel cell hydrogen supply systems.

Method used

By preparing nanometal oxide Ni3V2O8 doped aluminum hydride composite material, the interaction between Ni and V transition metals is used to create a polyvalent chemical environment in situ and improve the hydrogen release performance of aluminum hydride. The method includes preparing V2AlC precursors by solid phase sintering, preparing Ni3V2O8 catalyst by solvent thermal method, and mixing it with aluminum hydride by mechanical ball milling to form a composite hydrogen supply material.

Benefits of technology

The initial hydrogen discharge temperature of aluminum hydride is reduced to 72-75°C, and the hydrogen discharge amount and kinetic performance are improved. It is suitable for applications in the fields of portable fuel cells and drones.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118058A_ABST
    Figure CN119118058A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a nano metal oxide Ni3V2O8 doped aluminum hydride composite hydrogen donor material, aluminum hydride and nano metal oxide Ni3V2O8 are mixed and mechanically ball-milled to obtain the nano metal oxide Ni3V2O8 doped aluminum hydride composite hydrogen donor material, a nano metal oxide catalyst Ni3V2O8 is firstly prepared into a V2AlC precursor through a solid-phase sintering method, and then the nano metal oxide Ni3V2O8 doped aluminum hydride composite hydrogen donor material is prepared through a solvothermal method. The nano metal oxide catalyst Ni3V2O8 which is similar to a durian shell and is of a conical structure is creatively prepared, the catalyst has excellent catalytic activity, the initial hydrogen desorption temperature of a composite hydrogen supply material obtained after ball milling and aluminum hydride compounding is reduced to 72-75 DEG C, the hydrogen desorption amount reaches up to 8.2 wt%, the hydrogen desorption amount reaches up to 6.3 wt% at the temperature of 100 DEG C for 20 min, and the hydrogen desorption amount reaches up to 8.2 wt% at the temperature of 100 DEG C for 20 min. The hydrogen desorption performance is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of aluminum hydride hydrogen storage, and specifically relates to a nano metal oxide Ni 3 V 2 O 8 A method for preparing a composite hydrogen supply material doped with aluminum hydride. Background Art

[0002] Hydrogen energy is a secondary energy source with high energy density (142MJ / kg), clean zero carbon emissions, abundant sources, wide application range and various forms of utilization. It is considered to be an ideal energy storage method for achieving the low-carbon transformation of the energy system in the new era. However, the actual application of hydrogen energy is limited by the technical bottlenecks of its storage and transportation. Therefore, in order to achieve the widespread application of hydrogen energy, the development of safe and efficient hydrogen storage and transportation technology is a top priority. Solid-state hydrogen storage has the advantages of high energy density, good safety performance, easy storage and transportation, and is currently the most promising hydrogen storage method.

[0003] Among many solid-state hydrogen storage materials, aluminum hydride (AlH 3 ) has excellent mass hydrogen storage density (10.1wt%) and relatively mild hydrogen desorption temperature (150-200℃), and is currently one of the research hotspots in the field of solid-state hydrogen storage. It is an ideal hydrogen source for portable batteries and is expected to be used in military power supplies, military and civilian dual-use drones and other fields. However, as a hydrogen source for portable fuel cells, it has relatively high hydrogen desorption temperature and poor kinetic performance, which greatly hinders the development of AlH 3 Large-scale application. 3 Among the many methods to improve the hydrogen release performance, adding catalysts is a simple and effective modification method. Currently, the commonly used catalysts mainly include transition metal fluorides, oxides and rare earth metal oxides, which can effectively reduce AlH 3 The dehydrogenation temperature is reduced and the dehydrogenation kinetics are improved, but there is still a problem of high dehydrogenation termination temperature, which is not conducive to the practical application of portable fuel cell hydrogen supply systems (operating temperature 60-120°C).

[0004] Most transition metals have variable valence states due to the existence of unfilled valence d orbitals. Based on this characteristic, transition metal-based catalysts, such as vanadium-based catalysts, will produce intermediate valence active catalytic substances during the mechanical ball milling process with aluminum hydride, thereby improving the hydrogen desorption performance of aluminum hydride, reducing its hydrogen desorption operating temperature and hydrogen desorption reaction kinetics, thereby promoting its industrial application in the fields of drones, vehicle-mounted fuel cells, etc.

[0005] Based on this, the present invention is proposed. Summary of the invention

[0006] In view of the above technical problems, the present invention aims to provide a nano metal oxide Ni 3 V 2 O 8 Preparation method of aluminum hydride-doped composite hydrogen supply material, V 2 AlC precursor, and then Ni was prepared by solvothermal method 3 V 2 O 8 The catalyst is ball-milled with aluminum hydride to prepare the composite hydrogen supply material. The invention utilizes the interaction between Ni and V transition metals to create a multivalent chemical environment in situ to improve the hydrogen release performance of aluminum hydride, showing an excellent catalytic effect. The preparation process is simple and controllable, and is easy to promote and apply in industry.

[0007] To achieve the above object, the technical solution adopted by the present invention is:

[0008] A nano metal oxide Ni 3 V 2 O 8 The preparation method of the doped aluminum hydride composite hydrogen supply material is carried out in the following steps in sequence:

[0009] S1. Preparation of precursor V 2 AlC

[0010] V powder, Al powder and graphite powder were mixed uniformly in a molar ratio of 2:1.3:1, and V was prepared by solid phase sintering. 2 AlC powder;

[0011] S2. Preparation of Nano-Metal Oxide Catalyst Ni 3 V 2 O 8

[0012] Nickel nitrate hexahydrate was dissolved in 10% acetic acid solution, and then V 2 AlC powder was dispersed by ultrasound and then transferred to a hydrothermal reactor for solvent thermal reaction in a 200°C forced air drying oven. The product after the reaction was centrifuged, washed and dried, and the product was collected to obtain a nano-metal oxide catalyst Ni 3 V 2 O 8 ;

[0013] During the hydrothermal process, a durian-like cone-shaped structure Ni is formed. 3 V 2 O 8The hydrothermal reaction is a key process in which the hydrothermal reaction time, temperature, raw material ratio, etc. affect the composition and morphology of the product. When the hydrothermal reaction temperature is too low, the reaction is incomplete and impurities are present. When the hydrothermal reaction time is short, the raw materials are not completely reacted, a block structure exists, and a flaky structure is easily formed. When the reaction time is too long, the structure of the product will be destroyed, and growth and agglomeration will occur. When the raw material ratio is too high or too low, the reaction is prone to incomplete.

[0014] S3. Preparation of Nano-Metal Oxide Ni 3 V 2 O 8 Doped aluminum hydride composite hydrogen supply material

[0015] Aluminum hydride and nano-metal oxide catalyst Ni 3 V 2 O 8 The composite hydrogen supply material was prepared by mechanical ball milling under argon atmosphere.

[0016] As a limitation of the present invention, in step S1, the molar ratio of V powder, Al powder and graphite powder is 2:1.3:1, and the solid phase sintering method uses argon as the sintering atmosphere, firstly increases the temperature to 600°C at a heating rate of 5°C / min, and then increases the temperature to 1500°C at a heating rate of 10°C / min. The reaction temperature is 1500°C and the reaction time is 300min.

[0017] As a second limitation of the present invention, in step S2, nickel nitrate hexahydrate and V 2 The mass ratio of AlC powder is 93:15, the V 2 The size of AlC was 600 mesh.

[0018] The nickel nitrate hexahydrate of the present invention and V 2 The ratio of AlC powder is to form a durian shell-like cone structure Ni 3 V 2 O 8 The key is that when the ratio of the two is too large or too small, it is impossible to form a durian shell-like cone structure with uniform size and morphology. 3 V 2 O 8 .

[0019] As a third limitation of the present invention, in step S2, the hydrothermal reaction time is 30 hours.

[0020] The hydrothermal reaction time of the present invention also affects Ni 3 V 2 O 8 The key to morphology is that when the hydrothermal reaction time is too long or too short, it is impossible to form a durian shell-like cone structure with relatively uniform size and morphology. 3 V 2 O8 .

[0021] As a fourth limitation of the present invention, in step S2, the centrifugal washing is to wash the product with deionized water and anhydrous ethanol respectively for 4 to 6 times, each time centrifugation for 3 minutes.

[0022] As a fifth limitation of the present invention, in step S2, the drying temperature is 60° C. and the drying time is 24 hours.

[0023] As a sixth limitation of the present invention, in step S3, the nano metal oxide catalyst Ni 3 V 2 O 8 The doping amount is 5wt%.

[0024] As the seventh limitation of the present invention, in step S3, the ball-to-material ratio of the mechanical ball milling is 60:1, the ball milling speed is 350 r / min, the ball milling time is 1 h, and the volume of the ball milling jar is 250 mL.

[0025] Ball milling is the process of forming the final composite hydrogen-releasing material. During the ball milling process, Ni 3 V 2 O 8 With AlH 3 The interaction causes Ni 3 V 2 O 8 The +2-valent Ni and +5-valent V are transformed into Ni 2+ 、Ni 0 and V 4+ 、V 0 As catalytically active species, they synergistically enhance the AlH 3 Hydrogen release performance.

[0026] The present invention also has a limitation that the nano metal oxide catalyst Ni 3 V 2 O 8 It is a cone-shaped structure similar to the shell of a durian.

[0027] As is known to all, the morphology and structure of the product have a great influence on its performance. 3 V 2 O 8 It is a conical structure similar to the shell of a durian, which can promote the 3 The reduction of particle size leads to an increase in AlH 3 Improve the hydrogen decomposition performance, reduce the hydrogen decomposition temperature and improve the hydrogen decomposition kinetics.

[0028] The above technical solution of the present invention is taken as a whole, and each step is closely related and influences each other, which jointly determine the morphological characteristics and performance of the product.

[0029] The above technical solution has the following advantages or beneficial effects:

[0030] 1. The preparation method of the present invention is simple, the process is easy to control, the cycle is short, and it is easy to industrialize production and promote application.

[0031] 2. The catalyst Ni prepared by the present invention 3 V 2 O 8 Has excellent catalytic activity.

[0032] 3. The nano metal oxide Ni prepared by the present invention 3 V 2 O 8 The initial dehydrogenation temperature of the aluminum hydride-doped composite hydrogen supply material is reduced to 72-75°C, and the dehydrogenation amount is as high as 8.2wt%; the dehydrogenation amount in 20 minutes at 100°C is as high as 6.3wt%, which has excellent dehydrogenation performance.

[0033] The present invention is suitable for preparing nano metal oxide Ni 3 V 2 O 8 Doped aluminum hydride composite hydrogen supply material. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 V prepared in Example 1 of the present invention 2 AlC and Ni 3 V 2 O 8 -30h X-ray diffraction pattern;

[0035] Figure 2 Ni prepared in Example 1 3 V 2 O 8 -30h SEM and EDS images;

[0036] Figure 3 Ni prepared in Example 1 3 V 2 O 8 -30h XPS spectra of Ni 2p, V 2p and O1s;

[0037] Figure 4 is AlH in Examples 1 and 2 3 -5wt%Ni 3 V 2 O 8 -30h and AlH 3-5wt%V 2 Graph showing hydrogen desorption performance of AlC. DETAILED DESCRIPTION

[0038] The following embodiments are only some embodiments of the present invention, rather than all embodiments. Therefore, the detailed description in the embodiments of the present invention provided below is not intended to limit the scope of the present invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work belong to the protection scope of the present invention.

[0039] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.

[0040] Example 1 A nano metal oxide Ni 3 V 2 O 8 Preparation method of aluminum hydride-doped composite hydrogen supply material

[0041] S1, Precursor V 2 Preparation of AlC

[0042] V powder, Al powder and graphite powder were mixed uniformly in a molar ratio of 2:1.3:1. In a high-temperature tube furnace, with argon as the protective atmosphere, the temperature was raised to 600°C at a rate of 5°C / min, and then to 1500°C at a rate of 10°C / min. The temperature was kept at 1500°C for 300 min to prepare V by solid phase sintering. 2 AlC precursor, the prepared V 2 The AlC block solid was crushed, ground and passed through a 600-mesh sieve for subsequent experiments to obtain V 2 AlC powder;

[0043] S2, nano metal oxide catalyst Ni 3 V 2 O 8 Preparation

[0044] 0.93 g of nickel nitrate hexahydrate was added to 15 mL of 10% acetic acid solution and stirred at 500 rpm for 30 min at room temperature to form a uniform solution A. 0.15 g of V 2AlC powder was added to solution A, and ultrasonicated at a power of 500W for 30min to form a mixed solution B; the mixed solution B was transferred to a 25mL polytetrafluoroethylene reactor, sealed and placed in a blast drying oven at 200°C for 30h; after the reaction was completed and cooled to room temperature, it was centrifuged and washed with deionized water and anhydrous ethanol at a speed of 8000rpm and a single centrifugation time of 3min, first centrifuged with deionized water for 4 to 6 times, and then centrifuged with anhydrous ethanol for 2 to 3 times; finally, the obtained precipitate was placed in a vacuum drying oven at 60°C and dried for 24h to obtain the nano metal oxide catalyst Ni 3 V 2 O 8 , denoted as Ni 3 V 2 O 8 -30h;

[0045] S3, nano metal oxide Ni 3 V 2 O 8 Preparation of composite hydrogen-donating materials doped with aluminum hydride

[0046] With argon as the protective atmosphere and a pellet to material ratio of 60:1, 950 mg of aluminum hydride and 50 mg of Ni 3 V 2 O 8 The catalyst doping amount was 5 wt % and the composite hydrogen supply material was prepared by ball milling at a speed of 350 r / min for 1 h, which was denoted as AlH 3 -5wt%Ni 3 V 2 O 8 -30h.

[0047] The nano metal oxide catalyst Ni prepared in this example 3 V 2 O 8 Perform characterization assays, such as Figure 1 XRD test proves that after reaction, V 2 The characteristic peak of AlC disappears and Ni 3 V 2 O 8 The characteristic peaks of Ni 3 V 2 O 8 .

[0048] In order to demonstrate that the prepared nano-metal oxide catalyst Ni 3 V 2 O 8 The structural features of the Figure 2 As shown, Ni 3 V2 O 8 -30h presents a conical structure similar to the shell of a durian; EDS results show that Ni, V and O elements are evenly distributed.

[0049] In order to demonstrate that the prepared nano-metal oxide catalyst Ni 3 V 2 O 8 -30h chemical composition and valence state, and XPS test was performed on it. Figure 3 Ni in Example 1 3 V 2 O 8 XPS spectra of Ni 2p, V 2p and O1s at -30h show that V is V 5+ The Ni forms include Ni 2+ and satellite peaks, indicating that Ni 3 V 2 O 8 The catalyst was successfully prepared.

[0050] The Ni prepared in this example 3 V 2 O 8 The performance of the aluminum hydride-doped composite hydrogen supply material was measured, such as Figure 4 As shown, the initial dehydrogenation temperature is reduced to 72-75°C, and the dehydrogenation amount reaches 8.2wt%; at 100°C, the dehydrogenation amount in 20 minutes is 6.3wt%, which has excellent dehydrogenation performance.

[0051] Example 2-4 Nano-metal oxide Ni 3 V 2 O 8 Preparation method of aluminum hydride-doped composite hydrogen supply material

[0052] Preparation of Nano-Metal Oxide Catalyst Ni in Example 2-4 3 V 2 O 8 The specific process of doping aluminum hydride composite hydrogen supply material is similar to that of Example 1, except that the technical parameters in the preparation process are different.

[0053]

[0054] Comparative Example

[0055] In order to explore the effects of different parameters during the preparation of composite materials on their properties, the following groups conducted different experiments, as follows.

[0056] Group A: Preparation of AlH 3 -5wt%V 2The preparation process of AlC composite hydrogen storage material is similar to that of Example 1, except that: Step S2 is omitted, and the V prepared in Step S1 is directly 2 AlC was used as a catalyst to prepare V according to the process and proportion of S3. 2 AlC and aluminum hydride composite hydrogen storage material, denoted as AlH 3 -5wt%V 2 AlC.

[0057] Group B: AlH 3 Hydrogen storage material, without any catalyst added, denoted as AlH 3 -As-received.

[0058] Group C: Preparation of AlH 3 -5wt%Ni 3 V 2 O 8 The preparation process of the composite material is similar to that of Example 1, except that: the V prepared in step S1 2 AlC powder was purchased from commercial sources.

[0059] Group D: Preparation of AlH 3 -5wt%Ni 3 V 2 O 8 The preparation process of the composite material is similar to that of Example 1, except that: in step S1, nickel nitrate hexahydrate and V 2 The mass ratio of AlC powder is 62:5.

[0060] Group E: Preparation of AlH 3 -5wt%Ni 3 V 2 O 8 The preparation process of the composite material is similar to that of Example 1, except that: Step S1 prepares V 2 The molar ratio of the raw materials used for AlC powder is: V: Al: graphite powder = 2:1.2:1. The V used in step S2 is 2 AlC powder size: 300 mesh

[0061] Group F: Preparation of MgH 2 -5wt%Ni 3 V 2 O 8 The preparation process of the composite material is similar to that of Example 1, except that the hydrogen storage material in step S3 is replaced by MgH 2 .

[0062] The hydrogen release performance of the materials prepared by Group A and Group B was measured. The specific results are shown in Figure 4 As shown in the figure, we can know that: AlH 3-As-received sample's starting and ending dehydrogenation temperatures were 125 and 157 °C, respectively, and the dehydrogenation amount was 9.2 wt%. 2 After AlC, the starting and ending dehydrogenation temperatures were reduced to 92°C and 150°C, respectively, and the amount of dehydrogenation was reduced to 8.3wt%. 3 -As-received samples and AlH 3 -5wt%V 2 Compared with AlC samples, AlH 3 -5wt%Ni 3 V 2 O 8 The composite material has a more suitable hydrogen desorption temperature.

[0063] The performance of materials in groups C to F was measured, as shown in the table below.

[0064]

[0065] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein with equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a nano-metal oxide Ni3V2O8 doped aluminum hydride composite hydrogen supply material, characterized in that: Follow the steps below in order: S1. Preparation of precursor V2AlC V powder, Al powder and graphite powder were uniformly mixed in a molar ratio of 2:1.3:1, and V2AlC powder was prepared by a solid phase sintering method; S2. Preparation of Nano-Metal Oxide Catalyst Ni3V2O8 Nickel nitrate hexahydrate was dissolved in 10% acetic acid solution, and then V2AlC powder was added, and after ultrasonic dispersion, it was transferred to a hydrothermal reactor and subjected to a solvent thermal reaction in a 200°C forced air drying oven for 12 to 36 hours. The product after the reaction was centrifugally washed and dried, and the product was collected to obtain a nano-metal oxide catalyst Ni3V2O8; S3. Preparation of nano-metal oxide catalyst Ni3V2O8 doped aluminum hydride composite hydrogen supply material Aluminum hydride and nano-metal oxide catalyst Ni3V2O8 were mixed and a composite hydrogen supply material was prepared by mechanical ball milling in an argon atmosphere.

2. The method for preparing a nano-metal oxide catalyst Ni3V2O8 doped with aluminum hydride composite hydrogen supply material according to claim 1, characterized in that: In step S1, the molar ratio of V powder, Al powder and graphite powder is 2:1.3:1, and the solid phase sintering method uses argon as the sintering atmosphere. The temperature is first increased to 600°C at a heating rate of 5°C / min, and then increased to 1500°C at a heating rate of 10°C / min. The reaction temperature is 1500°C and the reaction time is 300min.

3. The method for preparing a nano-metal oxide catalyst Ni3V2O8 doped with aluminum hydride composite hydrogen supply material according to claim 1, characterized in that: In step S2, the mass ratio of nickel nitrate hexahydrate to V2AlC powder is 93:15, and the size of V2AlC is 600 mesh.

4. The method for preparing a nano-metal oxide catalyst Ni3V2O8 doped with aluminum hydride composite hydrogen supply material according to claim 1, characterized in that: In step S2, the centrifugal washing is performed using deionized water and anhydrous ethanol at a rotation speed of 8000 rpm and a single centrifugation time of 3 minutes, first centrifuging with deionized water for 4 to 6 times and then centrifuging with anhydrous ethanol for 2 to 3 times.

5. The method for preparing a nano-metal oxide catalyst Ni3V2O8 doped with aluminum hydride composite hydrogen supply material according to claim 1, characterized in that: In step S2, the drying temperature is 60° C. and the drying time is 24 hours.

6. The method for preparing a nano-metal oxide catalyst Ni3V2O8 doped with aluminum hydride composite hydrogen supply material according to claim 1, characterized in that: In step S3, the doping amount of the nano metal oxide catalyst Ni3V2O8 is 5wt%.

7. The method for preparing a nano-metal oxide catalyst Ni3V2O8 doped with aluminum hydride composite hydrogen supply material according to claim 1, characterized in that: In step S3, the ball-to-material ratio of the mechanical ball milling is 60:1, the ball milling speed is 350 r / min, the ball milling time is 1 h, and the volume of the ball milling jar is 250 mL.

8. The method for preparing a composite hydrogen supply material of nano metal oxide catalyst Ni3V2O8 doped with aluminum hydride according to any one of claims 1 to 7, characterized in that: The nano metal oxide catalyst Ni3V2O8 is a cone-shaped structure similar to the shell of a durian.

Citation Information

Patent Citations

  • Composite hydrogen storage material for complexing hydrides and hydrogen storage alloys

    CN101992056A

  • Aluminum hydride hydrogen storage material doped with transition metal fluoride and preparation method thereof

    CN103771337A

  • Aluminum hydride hydrogen storage material and preparation method thereof

    CN105645351A

  • Nanometer nickelous hydroxide doped composite hydrogen storage material and preparation method thereof

    CN107140601A

  • Regular quadrangular prism nickel vanadate nanomaterial and preparation method thereof

    CN108101123A